Epoxy resin composition, cured product, and semiconductor device

The epoxy resin composition with aliphatic hydrocarbon group-containing epoxy resin and inorganic filler addresses the challenge of high elastic modulus and water absorption in semiconductor encapsulation, improving thermal cycle resistance and crack resistance.

JP2025009528APending Publication Date: 2025-01-20NAMICS CORPORATION
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2023112595
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-07-07
Publication Date
2025-01-20

AI Technical Summary

Technical Problem

Existing epoxy resin compositions for semiconductor encapsulation face challenges in achieving a low elastic modulus and low water absorption, leading to issues such as cracks and defects in bump electrodes due to thermal stress, while reducing crosslinking density increases water absorbency and vapor pressure during solder reflow.

Method used

An epoxy resin composition comprising specific components like aliphatic hydrocarbon group-containing epoxy resin, other epoxy resins, a hardening agent, and inorganic filler, which together reduce elastic modulus and water absorption, improving thermal cycle resistance and crack resistance.

Benefits of technology

The composition achieves a cured product with low elastic modulus and low water absorption, enhancing thermal cycle resistance and reducing cracks in semiconductor devices, particularly during solder reflow processes.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025009528000007
    Figure 2025009528000007
  • Figure 2025009528000008
    Figure 2025009528000008
  • Figure 2025009528000009
    Figure 2025009528000009
Patent Text Reader

Abstract

To provide an epoxy resin composition that yields a cured product with low elastic modulus and low water absorption and also to provide a cured product with low elastic modulus and low water absorption.SOLUTION: An epoxy resin composition contains an epoxy resin (A) having an aliphatic hydrocarbon group with 5 or more carbon atoms, an epoxy resin (B) other than the epoxy resin (A), a curing agent (C), and an inorganic filler (D).SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an epoxy resin composition, and more specifically to an epoxy resin composition for semiconductor encapsulation, a cured product, and a semiconductor device. [Background technology]

[0002] As electronic devices become smaller, lighter, and more powerful, the mounting method of semiconductors is changing from wire bond type to flip chip type. Flip chip type semiconductor devices have a structure in which electrodes on a substrate are connected to a semiconductor element via bump electrodes. When heat is applied to such semiconductor devices, the difference in thermal expansion coefficient between the substrate and the semiconductor element causes stress to be applied to the bump electrodes, which causes defects such as cracks in the bump electrodes.

[0003] To prevent such defects, a semiconductor sealant called underfill is widely used (Patent Document 1). Underfill is a liquid sealant that is injected into the gap between the semiconductor element and the substrate and then thermally cured to fix the semiconductor element and the substrate together, thereby improving thermal cycle resistance. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2012-149111 A Summary of the Invention [Problem to be solved by the invention]

[0005] In addition, by reducing the elastic modulus of the cured product, the thermal cycle resistance tends to improve. One method for reducing the elastic modulus of the cured product is to adjust the components of the sealant to reduce the crosslink density of the cured product. However, this method increases the water absorption of the cured product, and as a result, the water contained in the cured product evaporates during the solder reflow process, and the pressure of the generated water vapor may cause cracks in the cured product. For these reasons, there is a demand for the creation of a sealant that can impart a low elastic modulus and low water absorption to the cured product.

[0006] Therefore, an object of the present invention is to provide an epoxy resin composition which gives a cured product having a low elastic modulus and low water absorption, and to provide a semiconductor device including the cured product having a low elastic modulus and low water absorption. [Means for solving the problem]

[0007] As a result of intensive research conducted by the present inventors to achieve the above object, it was discovered that a cured product of an epoxy resin composition containing a specific component has both low elastic modulus and low water absorption properties. The present invention was completed based on these findings.

[0008] That is, in the present invention, (A) an epoxy resin having an aliphatic hydrocarbon group having 5 or more carbon atoms; An epoxy resin (B) other than the above epoxy resin (A), A curing agent (C), and Inorganic filler (D), The epoxy resin composition includes:

[0009] The epoxy resin (A) preferably has an aliphatic hydrocarbon group having 5 to 20 carbon atoms.

[0010] The epoxy resin (A) preferably has two or more epoxy groups.

[0011] The epoxy resin (A) is preferably a cardanol-based epoxy resin.

[0012] The content of the epoxy resin (A) is preferably 5 to 80 mass % based on the total epoxy resins (100 mass %) contained in the epoxy resin composition.

[0013] The curing agent (C) is preferably at least one selected from the group consisting of amine-based curing agents, acid anhydride-based curing agents, phenol-based curing agents, and imidazole-based curing agents.

[0014] The content of the inorganic filler (D) is preferably 40 to 70% by mass relative to the epoxy resin composition (100% by mass).

[0015] The epoxy resin composition is preferably used for semiconductor encapsulation.

[0016] The present invention also provides a cured product of the above epoxy resin composition.

[0017] The present invention also provides a semiconductor device comprising a substrate, a semiconductor element disposed on the substrate, and the cured product that encapsulates the semiconductor element. Effect of the Invention

[0018] According to the epoxy resin composition of the present invention, a cured product having both low elastic modulus and low water absorption properties can be obtained. Therefore, when the epoxy resin composition is used for semiconductor encapsulation, the thermal cycle resistance of the semiconductor device is improved, and the occurrence of cracks in the cured product, semiconductor element, bump electrode, etc. is reduced. In addition, since the moisture content in the cured product is reduced, cracks are less likely to occur during the solder reflow process. [Brief description of the drawings]

[0019] [Figure 1] 1(a) to (c) are cross-sectional views illustrating an embodiment of a method for producing an electronic component according to the present invention. [Diagram 2] 2(a) and (b) are cross-sectional views showing another embodiment of the method for producing an electronic component according to the present invention. [Diagram 3] 3(a) to 3(c) are cross-sectional views showing one embodiment of a method for manufacturing a mounting board according to the present invention. [Figure 4] 4(a) to 4(c) are cross-sectional views showing another embodiment of the method for manufacturing a mounting board of the present invention. [Diagram 5] FIG. 5 is a cross-sectional image of the copper pillar in a direction perpendicular to the silicide layer (treated surface) in Example B10. [Figure 6] FIG. 6 is an enlarged view showing a schematic view of the treated surface of the "cross-sectional image in a direction perpendicular to the silicon compound layer (treated surface) of the copper pillar" in Example B10. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0020] <Epoxy resin composition> The present invention relates to an epoxy resin composition comprising an epoxy resin (A) having an aliphatic hydrocarbon group having 5 or more carbon atoms, an epoxy resin (B) other than the epoxy resin (A) having an aliphatic hydrocarbon group having 5 or more carbon atoms, a curing agent (C), and an inorganic filler (D). Hereinafter, the epoxy resin (A) having an aliphatic hydrocarbon group having 5 or more carbon atoms may be simply referred to as "epoxy resin (A)". The epoxy resin (B) other than the epoxy resin (A) may be simply referred to as "epoxy resin (B)".

[0021] [Epoxy resin (A)] The epoxy resin composition of the present invention can reduce the elastic modulus while suppressing the increase in water absorption of the cured product by containing the epoxy resin (A). The epoxy resin (A) has an aliphatic hydrocarbon group having 5 or more carbon atoms and an epoxy group as a substituent. Hereinafter, the aliphatic hydrocarbon group having 5 or more carbon atoms may be referred to as the "hydrocarbon group (a-1)". The epoxy group may be referred to as the "epoxy group (a-2)". The number of carbon atoms of the hydrocarbon group (a-1) is not particularly limited as long as it is 5 or more, but is preferably 8 or more, more preferably 10 or more, even more preferably 12 or more, and particularly preferably 14 or more. The number of carbon atoms of the hydrocarbon group (a-1) is preferably 20 or less, more preferably 18 or less, and even more preferably 16 or less. The number of carbon atoms is within the above range, that is, the hydrocarbon group (a-1) has a certain length, so that the epoxy resin (A) becomes hydrophobic, and the water absorption of the cured product tends to decrease. Furthermore, the crosslink density of the cured product tends to decrease, which decreases the elastic modulus. On the other hand, if the carbon number is less than 5, the crosslink density of the cured product tends to increase, and the elastic modulus tends to be high. In addition, the water absorption of the cured product tends to increase, and the occurrence of cracks during the solder reflow process tends to increase. If the carbon number of the hydrocarbon group (a-1) is 20 or less, the epoxy resin composition tends to have an appropriate viscosity and improved reactivity, probably due to improved compatibility with the epoxy resin (B). The epoxy resin (A) can be used alone or in combination of two or more types.

[0022] The hydrocarbon group (a-1) may be a linear, branched, or cyclic hydrocarbon group, but from the viewpoint of further reducing water absorption and elastic modulus, a linear or branched hydrocarbon group is preferred, and a linear hydrocarbon group is more preferred. The hydrocarbon group (a-1) may be a monovalent hydrocarbon group or a divalent or higher hydrocarbon group. The number of the hydrocarbon groups (a-1) in the epoxy resin (A) is not particularly limited as long as it is 1 or more, but is preferably 1 to 10. When the number of the hydrocarbon groups (a-1) is 2 or more, the epoxy resin (A) has a structure in which two or more hydrocarbon groups (a-1) are bonded by a linking group (excluding hydrocarbon groups). In this case, the hydrocarbon groups (a-1) may have the same structure or different structures.

[0023] The hydrocarbon group (a-1) may be either a saturated or unsaturated hydrocarbon group, but is preferably an unsaturated hydrocarbon group. When the hydrocarbon group (a-1) is an unsaturated hydrocarbon group, the number of double bonds that the hydrocarbon group (a-1) has is preferably 1 to 3.

[0024] The number of epoxy groups (a-2) in the epoxy resin (A) is not particularly limited as long as it is 1 or more, but from the viewpoint of reliability such as thermal cycle resistance, it is preferably 2 or more (i.e., it is a multifunctional epoxy resin). In addition, the number of epoxy groups in the epoxy resin (A) is not particularly limited, but is preferably, for example, 10 or less, and more preferably 5 or less.

[0025] The epoxy resin (A) may be in a liquid state or a solid state, but is preferably in a liquid state from the viewpoint of adjusting the viscosity of the epoxy resin composition.

[0026] The epoxy resin (A) can be rephrased as a compound in which the hydrocarbon group (a-1) and the epoxy group (a-2) are bonded via a single bond or a linking group. Examples of the linking group include divalent hydrocarbon groups (e.g., alkylene groups), aryl groups (-Ar-), carbonyl groups (-CO-), ether bonds (-O-), thioether bonds (-S-), ester bonds (-COO-), amide bonds (-CONH-), and groups in which a plurality of these are bonded together. However, the embodiment in which the hydrocarbon group (a-1) and the divalent hydrocarbon group are directly bonded to each other is excluded. The carbon number of the divalent hydrocarbon group is 1 to 4, preferably 1 to 3. The epoxy resin (A) may contain a compound having both a structure in which the hydrocarbon group (a-1) and the epoxy group (a-2) are bonded to each other via a single bond and a structure in which they are bonded to each other via a linking group in the molecule.

[0027] Among these, the epoxy resin (A) preferably has an aryl group from the viewpoint of improving the heat resistance and reducing the elastic modulus of the cured product. That is, the above-mentioned linking group in the epoxy resin (A) preferably contains an aryl group. Also, from the viewpoint of reducing the water absorption of the cured product, the above-mentioned linking group preferably contains an alkylene group and an ether bond, or contains an alkylene group, an aryl group, and an ether bond.

[0028] When the linking group in the epoxy resin (A) contains an alkylene group and an ether bond, the hydrocarbon group (a-1) is preferably a divalent or higher hydrocarbon group, more preferably a divalent hydrocarbon group. In this case, the epoxy resin (A) is preferably in a form in which an ether bond, an alkylene group, and an epoxy group (a-2) are bonded in this order, as viewed from the hydrocarbon group (a-1) side. The number of carbon atoms in the alkylene group is preferably 1 to 3, more preferably 1. An example of such an epoxy resin (A) is 1,6-hexanediol diglycidyl ether.

[0029] The epoxy resin (A) is preferably an epoxidized product of a phenolic hydroxyl group-containing compound or an epoxidized product of a polymer of a phenolic hydroxyl group-containing compound, and is preferably an epoxidized product of cardanol or a derivative thereof, or an epoxidized product of a polymer of cardanol or a derivative thereof. Hereinafter, the epoxidized product of cardanol or a derivative thereof, and the epoxidized product of a polymer of cardanol or a derivative thereof may be collectively referred to as "cardanol-based epoxy resin".

[0030] Cardanol is known as a compound contained in the shells of cashew nuts. Examples of cardanol and its derivatives contained in the shells of cashew nuts include compounds represented by the following formulas (1) to (4). In the formulas, R is one of the following four types of substituents, and the carbon at the left end is bonded to the phenyl group of the compounds represented by the following formulas (1) to (4).

[0031] [ka]

[0032] Examples of cardanol-based epoxy resins include compounds represented by the following formulae (CA1) and (CA2). The compound represented by the following formula (CA1) corresponds to an epoxidized product of cardanol or a derivative thereof, and the compound represented by the following formula (CA2) corresponds to an epoxidized product of a polymer of cardanol or a derivative thereof.

[0033] [ka]

[0034] In the above formula (CA1), R 1 R represents an aliphatic hydrocarbon group having 5 or more carbon atoms which may have a substituent. 2 represents an alkyl group, a carboxy group, or a hydroxyl group which may be protected by a protecting group. X represents a divalent hydrocarbon group (e.g., an alkylene group). n represents an integer of 0 to 3. When n is 2 or more, R 2 represent the same or different groups.

[0035] R 1 The "aliphatic hydrocarbon group having 5 or more carbon atoms" in the formula (a-1) is a substituent group described above as the hydrocarbon group (a-1). 1 R can be rephrased as an optionally substituted hydrocarbon group (a-1). 1 The substituent in is exemplified by a group containing an epoxy group (a-2). In this case, the epoxy group (a-2) may be bonded to the hydrocarbon group (a-1) via a single bond or a linking group, and the linking group may be an alkylene group, an aryl group (-Ar-), a carbonyl group (-CO-), an ether bond (-O-), a thioether bond (-S-), an ester bond (-COO-), an amide bond (-CONH-), or a group in which a plurality of these are linked. However, the embodiment in which the hydrocarbon group (a-1) and the alkylene group are directly bonded is excluded. The number of carbon atoms in the alkylene group is not particularly limited, but is preferably 1 to 5, and more preferably 1 to 3, for example. Among them, the linking group preferably contains an alkylene group, an aryl group, and an ether bond.

[0036] R 1 is not particularly limited, and examples thereof include monovalent saturated hydrocarbon groups such as heptan-1-yl, octan-1-yl, nonan-1-yl, decan-1-yl, undecane-1-yl, dodecane-1-yl, tetradecan-1-yl, and pentadecane-1-yl groups; monovalent unsaturated hydrocarbon groups such as pentadec-8-en-1-yl, pentadeca-8,11-dien-1-yl, pentadeca-8,11,14-trien-1-yl, pentadec-7-en-1-yl, pentadeca-7,10-dien-1-yl, and pentadeca-7,10,14-trien-1-yl groups; and groups in which one or more hydrogen atoms in the above-mentioned monovalent saturated or unsaturated hydrocarbon groups have been substituted with a substituent.

[0037] R 2Examples of the protecting group that the hydroxyl group in the formula (I) may have include alkyl groups having 1 to 4 carbon atoms, such as methyl, ethyl, and t-butyl groups, and groups that form an ester bond together with the oxygen atom constituting the hydroxyl group (for example, an acetyl group, a benzoyl group, etc.).

[0038] The number of carbon atoms in the alkylene group for X is not particularly limited, but is preferably 1 to 5, more preferably 1 to 3, and further preferably 1.

[0039] The compound represented by the formula (CA2) is a polymer obtained by polymerizing at least two or more compounds represented by the formula (CA1) alone or together with different compounds (monomers). The different compounds include, for example, formaldehyde.

[0040] In the above formula (CA2), R 11 , R 12 , R 13 are the same or different, and R 1 R represents an aliphatic hydrocarbon group having 5 or more carbon atoms which may have a substituent, as described above. 21 , R 22 , R 23 are the same or different, and R 2 X represents an alkyl group, a carboxy group, or a hydroxyl group which may be protected by a protecting group, as described above. 1 , X 2 , X 3 are the same or different and each represents an alkylene group as described above for X. n1, n2, and n3 are the same or different and each represents an integer of 0 to 3. When n1, n2, or n3 is 2 or more, R 21 , R 22 , R 23 Each represents the same or different group. L 1 and L 2 each independently represents a divalent linking group. m represents an integer of 1 or more, and preferably 1 to 5. When m is 2 or more, the structures in parentheses may be the same or different.

[0041] L 1 and L2 Examples of the divalent linking group include an alkylene group, a group derived from cardanol and its derivatives, and a group in which a plurality of these are linked together. The number of carbon atoms in the alkylene group is not particularly limited, but is preferably 1 to 5, more preferably 1 to 3, and even more preferably 1. Examples of the group derived from cardanol and its derivatives include groups in which two hydrogen atoms are substituted in the compounds represented by the above formulas (1) to (4).

[0042] R 11 , R 12 , R 13 In the above formula (CA1), the aliphatic hydrocarbon group having 5 or more carbon atoms which may have a substituent is R 1 Among these, an unsubstituted aliphatic hydrocarbon group having 5 or more carbon atoms is preferred. 21 , R 22 , R 23 The alkyl group, the carboxy group, and the hydroxyl group which may be protected by a protecting group in the above formula (CA1) include R 2 The examples given in the above are also preferred. 1 , X 2 , X 3 As the alkylene group in the above formula (CA1), those exemplified as X in the above formula (CA1) can be similarly mentioned as preferred examples.

[0043] The epoxy equivalent of the epoxy resin (A) is not particularly limited, but is, for example, preferably 50 to 1500 g / eq, more preferably 100 to 1200 g / eq, and further preferably 120 to 1000 g / eq.

[0044] Examples of the epoxy resin (A) include LITE514SE (bifunctional cardanol-based epoxy resin, epoxy equivalent 350 to 500 g / eq, manufactured by Cardrite Co., Ltd.), which is a compound represented by the following formula (CAC1), NC-547 (trifunctional cardanol-based epoxy resin, epoxy equivalent 800 g / eq, manufactured by Cardrite Co., Ltd.), which is a compound represented by the following formula (CAC2), and Epogosey HD (1,6-hexanediol diglycidyl ether, epoxy equivalent 150 to 160 g / eq, manufactured by Yokkaichi Synthetic Co., Ltd.).

[0045] [ka]

[0046] The content of the epoxy resin (A) is not particularly limited, but is preferably 5 to 80 mass%, more preferably 10 to 70 mass%, further preferably 10 to 60 mass%, and further preferably 10 to 50 mass%, based on the total epoxy resin (100 mass%) contained in the epoxy resin composition of the present invention. When the content of the epoxy resin (A) is within the above range, the elastic modulus and water absorption of the cured product tend to be reduced.

[0047] The content of the epoxy resin (A) relative to the epoxy resin composition of the present invention (100% by mass) is not particularly limited, but is, for example, preferably 1 to 50% by mass, more preferably 3 to 33% by mass, even more preferably 6 to 25% by mass, and even more preferably 10 to 20% by mass. When the content of the epoxy resin (A) is within the above range, the elastic modulus and water absorption of the cured product tend to be reduced.

[0048] [Epoxy resin (B)] The epoxy resin composition of the present invention can form a cured product with high electrical insulation by including the epoxy resin (B). The epoxy resin (B) is not particularly limited as long as it is an epoxy resin other than the epoxy resin (A), and examples thereof include aromatic epoxy resins and aliphatic epoxy resins. The number of epoxy groups in the epoxy resin (B) is not particularly limited as long as it is 1 or more, but from the viewpoint of reliability such as thermal cycle resistance, it is preferable that the number is 2 or more (i.e., it is a multifunctional epoxy resin). The epoxy resin (B) can be used alone or in combination of two or more.

[0049] The aromatic epoxy resin is not particularly limited as long as it is an epoxy resin having a structure containing an aromatic ring such as a benzene ring, but examples thereof include bisphenol A type epoxy resin, bisphenol F type epoxy resin, novolac type epoxy resin, fluorene type epoxy resin, biphenyl aralkyl epoxy resin, diepoxy resin such as 1,4-phenyldimethanol diglycidyl ether, biphenyl type epoxy resin such as 3,3',5,5'-tetramethyl-4,4'-diglycidyloxybiphenyl, glycidylamine type epoxy resin such as diglycidylaniline, diglycidyl toluidine, tetraglycidyl-m-xylylenediamine, aminophenol type epoxy resin such as triglycidyl-p-aminophenol, and naphthalene ring-containing epoxy resin. Among them, bisphenol A type epoxy resin, bisphenol F type epoxy resin, biphenyl type epoxy resin, aminophenol type epoxy resin, and naphthalene ring-containing epoxy resin are preferred.

[0050] The aliphatic epoxy resin is not particularly limited, and examples thereof include diepoxy resins such as polytetramethylene glycol diglycidyl ether, polypropylene glycol diglycidyl ether, butanediol diglycidyl ether, neopentyl glycol diglycidyl ether, trimethylolpropane diglycidyl ether, glycerin diglycidyl ether, neopentyl glycol diglycidyl ether, and 1,4-cyclohexanedimethanol diglycidyl ether; trimethylolpropane triglycidyl ether, and glycerin triglycidyl ether. triepoxy resins such as vinyl(3,4-cyclohexene) dioxide, alicyclic epoxy resins such as 2-(3,4-epoxycyclohexyl)-5,1-spiro-(3,4-epoxycyclohexyl)-m-dioxane, glycidylamine-type epoxy resins such as tetraglycidylbis(aminomethyl)cyclohexane, hydantoin-type epoxy resins such as 3-diglycidyl-5-methyl-5-ethylhydantoin, and epoxy resins having a silicone skeleton such as 1,3-bis(3-glycidoxypropyl)-1,1,3,3-tetramethyldisiloxane. Among these, 1,4-cyclohexanedimethanol diglycidyl ether and polytetramethylene glycol diglycidyl ether are preferred.

[0051] The epoxy resin composition of the present invention may or may not contain an epoxy compound represented by the following formula (X) as the aromatic epoxy resin.

[0052] [ka]

[0053] In the above formula, R X1 and R X2 each independently represents an alkylene group having 2 to 4 carbon atoms; R X3 represents a methylene group or -C(CH3)2-, and a and b each independently represent an integer of 1 to 10.

[0054] The epoxy equivalent of the epoxy resin (B) is not particularly limited, but is, for example, preferably 30 to 1000 g / eq, more preferably 40 to 600 g / eq, and further preferably 50 to 500 g / eq.

[0055] The content of the epoxy resin (B) is not particularly limited, but is preferably 20 to 95 mass%, more preferably 30 to 90 mass%, further preferably 40 to 90 mass%, and further preferably 50 to 90 mass%, based on 100 mass% of the total epoxy resin contained in the epoxy resin composition of the present invention. When the content of the epoxy resin (B) is within the above range, the elastic modulus and water absorption of the cured product tend to be reduced.

[0056] The content of the epoxy resin (B) relative to the epoxy resin composition of the present invention (100% by mass) is not particularly limited, but is, for example, preferably 3 to 50% by mass, more preferably 6 to 45% by mass, and further preferably 10 to 40% by mass. When the content of the epoxy resin (B) is within the above range, the elastic modulus and water absorption of the cured product tend to be reduced.

[0057] The content of all epoxy resins in the epoxy resin composition of the present invention (100% by mass) is not particularly limited, but is, for example, preferably 5 to 80% by mass, more preferably 10 to 70% by mass, and further preferably 15 to 60% by mass. When the total epoxy resins, i.e., the total content of the epoxy resins contained in the epoxy resin composition of the present invention, is within the above range, the epoxy resin composition exhibits good curability, and the elastic modulus and water absorption of the cured product tend to be reduced.

[0058] [Hardening agent (C)] The curing agent (C) is not particularly limited as long as it initiates, advances, or accelerates the polymerization of the epoxy resin, and examples thereof include amine-based curing agents, acid anhydride-based curing agents, phenol-based curing agents, and imidazole-based curing agents. The curing agent (C) may be used alone or in combination of two or more.

[0059] Examples of the amine-based curing agent include aromatic amines such as methylenedianiline, m-phenylenediamine, 4,4'-diaminodiphenylsulfone, 4,4'-diamino-3,3'-diethyldiphenylmethane, diethyltoluenediamine, dimethylthiotoluenediamine, and 3,3'-diaminodiphenylsulfone. Examples of the acid anhydride-based curing agent include alkylated tetrahydrophthalic anhydrides such as methyltetrahydrophthalic anhydride and methylhexahydrophthalic anhydride, hexahydrophthalic anhydride, methylhymic anhydride, dodecenyl succinic anhydride, and methylnadic anhydride. Examples of the phenol-based curing agent include phenol novolac resin, cresol novolac resin, naphthol-modified phenolic resin, dicyclopentadiene-modified phenolic resin, and p-xylene-modified phenolic resin. Examples of the imidazole-based hardener include 2-methylimidazole, 2-undecylimidazole, 1-cyanoethyl-2-undecylimidazole, 2-heptadecylimidazole, 2-ethyl-4-methylimidazole, 1-cyanoethyl-2-ethyl-4-imidazole, 2-phenylimidazole, and 2-phenyl-4-methylimidazole. Examples of the imidazole-based hardener include microcapsule-type imidazole-based hardener.

[0060] The content of the curing agent (C) is not particularly limited, but for example, it is preferably 1 to 200 parts by mass, and more preferably 2 to 150 parts by mass, relative to 100 parts by mass of all the epoxy resins contained in the epoxy resin composition of the present invention.

[0061] The content of the curing agent (C) relative to the epoxy resin composition of the present invention (100 mass%) is not particularly limited, but is, for example, preferably 0.1 to 60 mass%, more preferably 0.3 to 50 mass%, further preferably 0.5 to 40 mass%, and particularly preferably 1 to 30 mass%.

[0062] [Inorganic filler (D)] The inorganic filler (D) is not particularly limited, but is preferably one that has the property of suppressing the volume shrinkage (curing shrinkage) caused by the curing reaction of the epoxy resin composition, one that has the property of suppressing the volume change (thermal shrinkage) caused by heat of the cured product, or one that has both of these properties. Examples of the inorganic filler (D) include silica, silicon carbide, silicon nitride, alumina (aluminum oxide), aluminum nitride, aluminum hydroxide, aluminum silicate, magnesium silicate, calcium silicate, calcium carbonate, barium sulfate, barium carbonate, titanium oxide, lime sulfate, potassium titanate, magnesium carbonate, zinc oxide, boron nitride, zirconia (zirconium oxide), and inorganic particles whose surfaces are treated with these. The inorganic filler (D) can be used alone or in combination of two or more types.

[0063] In order to keep the viscosity of the epoxy resin composition within an appropriate range, the inorganic filler (D) is preferably surface-treated with a coupling agent having a functional group such as an epoxy group, a (meth)acryloyl group, or an amino group (particularly a phenylamino group). Examples of the coupling agent include silane coupling agents such as 3-glycidoxypropyltrimethoxysilane, 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, 3-methacryloxypropyltrimethoxysilane, and N-phenyl-3-aminopropyltrimethoxysilane. For the surface treatment of the inorganic filler (D), one of the above coupling agents can be used alone, or two or more of them can be used in combination.

[0064] The shape of the inorganic filler (D) is not particularly limited, but examples thereof include a spherical shape (such as a true spherical shape or a nearly true spherical shape), a polyhedral shape, a rod shape (such as a cylindrical shape or a prismatic shape), a flat plate shape, a scale shape, and an irregular shape. Among these, a spherical shape is preferable from the viewpoint of increasing the loading amount.

[0065] The average particle size of the inorganic filler (D) is not particularly limited, but is preferably 1 nm to 5.0 μm, and more preferably 3 nm to 3.0 μm. When the average particle size of the inorganic filler (D) is within the above range, the epoxy resin composition has an appropriate viscosity, and the problem of speed reduction during injection into the gap is unlikely to occur. When the average particle size is within the above range, the epoxy resin composition has an appropriate viscosity, and there is a tendency that the injection speed is unlikely to decrease. In this specification, the method for measuring the average particle size of the inorganic filler (D) is not particularly limited, but can be measured, for example, using a laser diffraction / scattering particle size distribution measuring device (product name: LS 13 320, manufactured by Beckman Coulter).

[0066] When the inorganic filler (D) contains an inorganic filler (D-1) having an average particle size of 0.5 μm to 5.0 μm and an inorganic filler (D-2) having an average particle size of 1 nm or more and less than 0.5 μm, it is preferable in that the viscosity of the epoxy resin composition is in an appropriate range. The average particle size of the inorganic filler (D-1) is preferably 0.5 μm to 3.0 μm. The average particle size of the inorganic filler (D-2) is preferably 5 nm to 0.4 μm, more preferably 7 nm to 0.3 μm.

[0067] The content of the inorganic filler (D) relative to the epoxy resin composition of the present invention (100% by mass) is not particularly limited, but is preferably 30% by mass or more, more preferably 40% by mass or more, even more preferably 50% by mass or more, and particularly preferably 60% by mass or more. When the content of the inorganic filler (D) is within the above range, the curing shrinkage and heat shrinkage of the cured product tend to be suppressed, and further, the water absorption tends to be reduced, so that the thermal cycle resistance tends to be improved.

[0068] The content of the inorganic filler (D) relative to the epoxy resin composition of the present invention (100 mass%) is not particularly limited, but from the viewpoints of ensuring an appropriate viscosity as an epoxy resin composition and improving workability when preparing the epoxy resin composition, it is preferably less than 77 mass%, more preferably 75 mass% or less, and from the viewpoint of low elasticity, it is preferably 70 mass% or less.

[0069] Among these, when the content of the inorganic filler (D) is 40 to 70 mass% relative to the epoxy resin composition (100 mass%), the elastic modulus and water absorption of the cured product are both reduced, and the epoxy resin composition has an appropriate viscosity, which tends to particularly improve workability.

[0070] [Other ingredients] The epoxy resin composition of the present invention may contain components other than the epoxy resin (A), the epoxy resin (B), the curing agent (C), and the inorganic filler (D) (hereinafter referred to as "other components (E)"). Examples of the other components (E) include curable compounds other than the epoxy resin (A) and the epoxy resin (B), thermoplastic resins such as polyethylene resins, polyester resins, polyurethane resins, and polyamide resins, coupling agents, ion trapping agents, leveling agents, antioxidants, defoamers, flame retardants, colorants, reactive diluents, elastomers, solvents, etc. The other components (E) may be used alone or in combination of two or more.

[0071] The content of the other component (E) relative to the epoxy resin composition of the present invention (100 mass%) is not particularly limited as long as it does not impair the effects of the present invention. For example, the content is preferably 0.001 to 10 mass%, more preferably 0.01 to 5 mass%, and even more preferably 0.1 to 3 mass%.

[0072] [Physical properties and production method of epoxy resin composition] The viscosity of the epoxy resin composition of the present invention (25°C, Brookfield viscometer, 50 rpm) is not particularly limited, but is preferably, for example, 1 to 200 Pa s, and more preferably 1 to 100 Pa s. When the viscosity is within the above range, injection into gaps tends to be easy.

[0073] The epoxy resin composition of the present invention can be prepared by a known and commonly used method. For example, the epoxy resin (A), the epoxy resin (B), the curing agent (C), the inorganic filler (D), and other components (E) as required are simultaneously or separately introduced into an appropriate mixer, and stirred and mixed while melting by heating as required, to obtain the epoxy resin composition of the present invention. When the epoxy resin (A) is solid, it is preferable to heat it to liquefy or fluidize it before mixing. When it is difficult to uniformly disperse the inorganic filler (D) in the epoxy resin composition, the epoxy resin and the inorganic filler (D) may be heated and mixed to uniformly disperse the inorganic filler (D) in the epoxy resin, and then cooled as required, and further components such as the curing agent (C) may be mixed to prepare the epoxy resin composition of the present invention.

[0074] The mixer is not particularly limited, and examples thereof include a roll mill equipped with a stirrer and a heater, a Raikai mixer, a Henschel mixer, a tumbler, a planetary mixer, etc. The mixing ratio of each component is appropriately set according to the content of each component in the epoxy resin composition.

[0075] The epoxy resin composition of the present invention can be preferably used as a material for sealing a semiconductor element arranged on a substrate in a semiconductor device (an epoxy resin composition for semiconductor sealing). By using the epoxy resin composition of the present invention as an epoxy resin composition for semiconductor sealing, a sealed body having excellent thermal cycle resistance and crack resistance can be produced. In addition, the epoxy resin composition of the present invention can be preferably used as a material for sealing a semiconductor element arranged on a substrate in a flip-chip type semiconductor device (an epoxy resin composition for flip-chip type semiconductor sealing). Specifically, by injecting the epoxy resin composition of the present invention into the gap between a semiconductor element and a substrate and subjecting it to thermal curing, the bump electrodes present in the gap can be sealed while the semiconductor element and the substrate can be fixed to each other as a sealed body, thereby improving thermal cycle resistance.

[0076] Examples of the epoxy resin composition for semiconductor encapsulation include underfills such as capillary underfill, liquid mold underfill, secondary underfill, and pre-applied underfill, as well as grab top agents and liquid compression molding agents. The epoxy resin composition of the present invention is not limited to the above-mentioned use as an epoxy resin composition for semiconductor encapsulation, and can be used, for example, as an adhesive for fixing, joining, or protecting components constituting electronic components.

[0077] [Cured product] A cured product is obtained by curing the epoxy resin composition of the present invention. The curing method is not particularly limited, but for example, the epoxy resin composition is subjected to a heat treatment. The heat treatment temperature is not particularly limited, but for example, 60 to 200°C is preferable, and 80 to 180°C is more preferable. The heat treatment time is not particularly limited, but for example, 0.1 to 5 hours is preferable, and 0.5 to 3 hours is more preferable.

[0078] The water absorption rate (%) of the cured product is not particularly limited, but is preferably less than 3.0%, more preferably 2.8% or less, and even more preferably 2.6% or less. The water absorption rate (%) of the cured product is not particularly limited, but may be, for example, 0.1% or more, 0.3% or more, or 0.6% or more. The water absorption rate (%) can be measured by the method described in the examples.

[0079] The elastic modulus (GPa) of the cured product at 25°C is not particularly limited, but is preferably less than 9.0GPa, more preferably 8.9GPa or less, and even more preferably 8.8GPa or less. The elastic modulus (GPa) of the cured product at 25°C is not particularly limited, but is preferably 1GPa or more, more preferably 3GPa or more, and even more preferably 4GPa or more. The elastic modulus (GPa) at 25°C can be measured by the method described in the examples.

[0080] [Semiconductor Devices] The semiconductor device of the present invention comprises a substrate, a semiconductor element disposed on the substrate, and a cured product of the epoxy resin composition of the present invention that encapsulates the semiconductor element. The semiconductor device is preferably a flip-chip type semiconductor device. The flip-chip type semiconductor device has a structure in which an electrode portion on a substrate and a semiconductor element are connected via bump electrodes.

[0081] The epoxy resin composition of the present invention is injected into the gap between the semiconductor element and the substrate and thermally cured to form a cured product (sealant). The method of injecting the epoxy resin composition of the present invention into the gap is not particularly limited, but for example, the epoxy resin composition is applied to one end of the substrate or the semiconductor element while heating the substrate to 50 to 120°C, and the epoxy resin composition fills the gap between the substrate and the semiconductor element by capillary action. After filling the gap with the epoxy resin composition of the present invention, the substrate is heated at a predetermined temperature for a predetermined time, specifically, at the temperature and time described in the heat treatment of the cured product, to seal the gap.

[0082] <Electronic components with copper pillars> Hereinafter, the invention of "electronic component having a copper pillar" will be described. More specifically, an electronic component having a copper pillar (X) and a silicon compound layer (Y) covering at least a part of the copper pillar (X) is provided. Hereinafter, the electronic component may be referred to as "electronic component of the present invention".

[0083] A flip-chip type semiconductor device has a structure in which an electrode portion on a substrate and a semiconductor element are connected via bump electrodes. A known bump electrode includes a copper pillar, and the copper pillar is provided on an electronic component such as a semiconductor chip. Such an electronic component is mounted by connecting it to a plurality of electrodes arranged on the surface of a wiring substrate via solder bumps. The underfill is injected between the electronic component and the wiring substrate, and becomes a hardened material (sealing body) by applying heat curing. The underfill is required not to peel off at the interface with the electronic component or the wiring substrate, and not to crack the sealing body when mounted on the substrate. The underfill is also required to have high adhesion to the copper pillar.

[0084] It is known that silsesquioxane having an epoxy group is blended into the underfill in order to improve adhesion to the copper pillar (Patent Document 2 described below). However, even when such an underfill is used, it is difficult to suppress delamination (interlayer peeling) between the sealing body and the copper pillar after reflow. In addition, a method is known in which delamination between the sealing body and the copper pillar is suppressed by increasing the glass transition temperature of the underfill. However, increasing the glass transition temperature of the underfill makes it difficult to harden it at a low temperature, narrowing the range of blend design. For this reason, there is a demand for suppressing delamination by means other than adjusting the glass transition temperature.

[0085] Patent Document 2: JP 2010-147175 A

[0086] Therefore, an object of the present invention is to provide an electronic component having a copper pillar that can suppress delamination (interlayer peeling) between the sealing body and the copper pillar after reflow. Another object of the present invention is to provide a mounting board in which delamination between the sealing body and the copper pillar is unlikely to occur.

[0087] As a result of intensive research to achieve the above object, the inventors have found that by performing a specific treatment on an electronic component having a copper pillar, it is possible to suppress delamination (interlayer peeling) between the sealing body and the copper pillar after reflow. The present invention was completed based on these findings.

[0088] That is, the present invention provides the following. [1] Copper pillar (X) and A silicon compound layer (Y) covering at least a part of the copper pillar (X); An electronic component comprising: [2] The electronic component according to [1], further comprising a copper oxide layer (Z) between the copper pillar (X) and the silicon compound layer (Y). [3] The electronic component according to [1] or [2], wherein the silicon compound layer (Y) contains water glass and a silane coupling agent. [4] The electronic component according to [3], wherein the silane coupling agent is at least one selected from the group consisting of 3-aminopropyltriethoxysilane, 3-glycidoxypropyltrimethoxysilane, 3-aminopropyltrimethoxysilane, and 3-mercaptopropylmethyldimethoxysilane. [5] The electronic device according to any one of [2] to [4], wherein the copper oxide layer (Z) is a layer formed by an oxidation treatment of the copper pillar (X). [6] The electronic component according to any one of [1] to [5], wherein the silicon compound layer (Y) is a layer formed by subjecting the copper pillar (X) and / or the copper oxide layer (Z) to a water glass treatment and / or a silane coupling treatment. [7] The electronic component according to any one of [1] to [6], wherein the average height difference of the copper pillar (X) surface is 5 nm or more, 10 nm or more, or 21 nm or more, and / or 500 nm or less, 450 nm or less, or 405 nm or less. [8] An electronic component according to any one of [1] to [7]; A substrate having an electrode portion, the electrode portion being connected to the electronic component via the copper pillar (X); a sealing body located between the electronic component and the substrate; A mounting board comprising: [9] A mounting board, wherein the sealing body according to [8] is a cured underfill.

[10] A method for manufacturing an electronic component, comprising the following steps: A silicon compound layer (Y) formation step for forming a silicon compound layer (Y) on an electronic component having a copper pillar (X) by water glass treatment and / or silane coupling treatment.

[11] A method for producing an electronic component according to

[10] , further comprising the steps of: A copper oxide layer (Z) formation process for forming a copper oxide layer (Z) by oxidation treatment on an electronic component having a copper pillar (X).

[12] The method for producing an electronic component according to

[10] or

[11] , wherein the silane coupling agent is at least one selected from the group consisting of 3-aminopropyltriethoxysilane, 3-glycidoxypropyltrimethoxysilane, 3-aminopropyltrimethoxysilane, and 3-mercaptopropylmethyldimethoxysilane.

[13] A method for manufacturing a mounting substrate, comprising the following steps: A step of connecting the copper pillar (X) of the electronic component according to any one of [1] to [7] to an electrode portion of a substrate having an electrode portion. A process of injecting an underfill between the electronic component and the substrate, and then heat-curing the underfill to form a sealed body.

[0089] According to the electronic component of the present invention, it is possible to suppress delamination (interlayer peeling) between the sealing body and the copper pillar after reflow. Also, the mounting board of the present invention has a feature that delamination between the sealing body and the copper pillar is unlikely to occur.

[0090] [Electronic components] The electronic component of the present invention comprises a copper pillar (X) and a silicon compound layer (Y) covering at least a part of the copper pillar (X). Furthermore, a copper oxide layer (Z) may be included between the copper pillar (X) and the silicon compound layer (Y). In the mounting substrate, the copper pillar (X) serves as a terminal for electrically connecting the electronic component to an electrode part of the substrate. The mounting substrate also comprises a sealing body between the electronic component and the substrate, and at least a part of the silicon compound layer is in contact with the sealing body. Examples of the sealing body include a liquid sealing agent (liquid sealing material) such as an underfill, a film-like sealing material, and a granular sealing material. The liquid sealing agent becomes a sealing body by hardening. The film-like sealing material is attached to the electronic component or substrate, and melted and cooled as necessary to become a sealing body. The granular sealing material is inserted between the electronic component and the substrate, and melted and cooled as necessary to become a sealing body.

[0091] [Copper pillar (X)] The copper pillar (X) is a pillar containing copper. More specifically, it is a pillar made of copper or a copper alloy. The copper pillar (X) is not particularly limited as long as it functions as the above-mentioned terminal, and may be a copper post, a copper pin, or the like. The method of forming the copper pillar (X) on the electronic component is not particularly limited, and examples thereof include electrolytic plating, electroless plating, cutting processing, and the like.

[0092] The copper pillar (X) may have a bump made of a low melting point metal such as solder or lead-free solder such as Sn-In, Sn-Zn, Sn-Sb, Sn-Cu, Sn-Ag-Cu, Sn-Cu-Ni, and Sn-Bi at its tip when viewed from the electronic component side (FIG. 2(a)). When the copper pillar (X) has the bump, the silicon compound layer (Y) may have a form covering at least a part of the bump.

[0093] The average height difference of the copper pillar (X) surface is not particularly limited, but is preferably 5 nm or more, more preferably 10 nm or more, and even more preferably 21 nm or more. Also, it is preferably 500 nm or less, more preferably 450 nm or less, and even more preferably 405 nm or less. The average height difference of the copper pillar (X) surface can be measured, for example, by the following method. A cross-sectional image of the copper pillar in a vertical direction to the silicon compound layer (treated surface) is taken using a scanning electron microscope (SEM). In the cross-sectional image, a straight line (L1) that touches the two lowest concave points and a straight line (L2) that touches the highest convex point and is parallel to the straight line (L1) are drawn. The perpendicular distance (D) between the straight lines (L1) and (L2) is measured. Furthermore, the perpendicular distance is measured for five different points of the copper pillar by the same method. The magnification of the cross-sectional image in the measurement is not particularly limited, but it is preferable to set it to, for example, 5,000 to 60,000 times in order to calculate an accurate value. By averaging the vertical distances (height differences) obtained by these operations, the average height difference of the surface of the copper pillar (X) can be calculated. When the average height difference is small, the shape of the copper pillar (X) does not change, which is preferable from the viewpoint of connectivity and pitch not becoming narrower.

[0094] [Silicon compound layer (Y)] The silicon compound layer (Y) is a layer containing a silicon compound. In the silicon compound layer (Y), "containing a silicon compound" includes not only the silicon compound itself, but also a part of the silicon compound is chemically bonded to the surface of the copper pillar (X) and / or the copper oxide layer (Z). Therefore, it includes a case where water glass (i.e., sodium silicate) is chemically bonded to the surface of the copper pillar (X) and / or the copper oxide layer (Z) by the water glass treatment and / or silane coupling treatment described later, and a case where a part of the silane coupling agent is chemically bonded to the surface of the copper pillar (X) and / or the copper oxide layer (Z). The silicon compound layer (Y) may be formed by the water glass treatment and / or silane coupling treatment of the copper pillar (X) and / or the copper oxide layer (Z). By including the silicon compound layer (Y), the electronic component of the present invention can significantly suppress the occurrence of delamination between the sealing body and the copper pillar after reflow. The electronic device of the present invention may have at least one silicon compound layer (Y), or may have two or more silicon compound layers (Y).

[0095] Examples of the silicon compounds include Si compounds such as SiO, SiO2, and SiO4. x O y Silicon oxide represented by the formula: SiO4H4, Si2O7H6, SiO3H2, Si2O5H2, etc. x O y H zExamples of the silicon hydroxide represented by the formula (I) are inorganic silicon compounds such as water glass (Na2SiO3); organic silicon compounds such as alkoxysilanes, silane coupling agents, polyether-modified silicones, silicon carbides, silicon sulfides, and silicon nitrides; and silicon halides. Examples of the silane coupling agents include 3-aminopropyltriethoxysilane, 3-glycidoxypropyltrimethoxysilane, 3-aminopropyltrimethoxysilane, and 3-mercaptopropylmethyldimethoxysilane. An example of an embodiment in which a part of the silicon compound is chemically bonded to the surface of the copper pillar (X) and / or the copper oxide layer (Z) is an embodiment in which a SiO group derived from a silane coupling agent is chemically bonded to the surface of the copper pillar (X) and / or the copper oxide layer (Z). In the silicon compound layer (Y), the silicon compounds can be used alone or in combination of two or more.

[0096] A method for confirming the silicon compound layer (Y), that is, a method for confirming whether the silicon compound layer (Y) contains a silicon compound, may be, for example, elemental analysis by time-of-flight secondary ion mass spectrometry (TOF-SIMS) or X-ray photoelectron spectroscopy (XPS). When the silicon compound layer (Y) is formed on the surface of the copper pillar (X), elemental analysis of the copper pillar (X) surface by TOF-SIMS detects silicon compounds such as silicon oxide and silicon hydroxide. Furthermore, elemental analysis of the copper pillar (X) surface by XPS detects Si2p derived from the silicon compound. Usually, molecules within 1 nm from the surface are analyzed in TOF-SIMS, and molecules within several nm to several tens of nm (for example, within 10 nm or within 20 nm) from the surface are analyzed in XPS. The analysis conditions for TOF-SIMS and XPS are not particularly limited and can be appropriately determined by a person skilled in the art, but it is preferable to perform the analysis under the conditions described in the Examples, for example. The method for confirming the silicon compound layer (Y) is not limited to TOF-SIMS and XPS, and any method for detecting or analyzing the presence of silicon compounds or silicon from the target sample can be used.

[0097] In the elemental analysis by XPS, the content of Si2p measured from the silicon compound layer (Y) is not particularly limited, but is preferably 0.3 at% or more, more preferably 0.5 at% or more, relative to the total of the detected components. The content of Si2p is preferably 15 at% or less, more preferably 10 at% or less, and even more preferably 7.1 at% or less. When the content of Si2p is within the above range, the occurrence rate of delamination between the sealing body and the copper pillar after reflow tends to be reduced. In particular, when the content of Si2p is 0.3 at% or more, the amount of the silicon compound layer formed is sufficient, and the effect of suppressing delamination between the sealing body and the copper pillar after reflow tends to be high. In addition, when the content of Si2p is 15 at% or less, the amount of the silicon compound layer formed is appropriate, and peeling between the copper pillar (X) and the silicon compound layer (Y), or peeling between the silicon compound layers (Y) when the silicon compound layer (Y) is two or more layers, tends to be less likely to occur.

[0098] [Copper oxide layer (Z)] The copper oxide layer (Z) is a layer containing copper oxide. In the copper oxide layer (Z), "containing copper oxide" includes not only an embodiment in which copper oxide itself is contained, but also an embodiment in which a part of the copper oxide is chemically bonded to the surface of the copper pillar (X) and an embodiment in which the copper oxide is formed by oxidizing the surface of the copper pillar (X).

[0099] Generally, the surface of the copper pillar is naturally oxidized to form a copper oxide layer. In the electronic component of the present invention, the copper oxide layer (Z) may be formed by natural oxidation, but is preferably formed by an artificial operation (e.g., oxidation treatment). The copper oxide layer (Z) formed by an artificial operation such as oxidation treatment tends to improve wettability by forming fine irregularities on its surface, and is therefore preferable from the viewpoint of adhesion and adhesion to the sealing body. On the other hand, the copper oxide layer (Z) formed by natural oxidation has a flat surface and tends to become brittle and peel off easily. Therefore, in consideration of the formation of the silicon compound layer (Y), it is preferable to remove the copper oxide layer (Z) formed by natural oxidation.

[0100] The copper oxide contained in the copper oxide layer (Z) is not particularly limited, and examples thereof include copper oxide (CuO) and cuprous oxide (CuO). The above copper oxides can be used alone or in combination of two or more.

[0101] The copper oxide layer (Z) may contain copper hydroxide (Cu(OH)2). When the copper oxide layer (B) contains copper hydroxide, the silicon compound contained in the silicon compound layer (Y) and the copper hydroxide undergo dehydration condensation, which tends to improve the adhesive strength between the silicon compound layer (Y) and the copper oxide layer (Z), thereby enhancing the effect of suppressing delamination.

[0102] [Electronic component manufacturing method] The method for producing an electronic device of the present invention includes the following silicon compound layer (Y) forming step, and may also include the following pretreatment step and / or copper oxide layer (Z) forming step. A pre-treatment process for electronic components with copper pillars (X) A copper oxide layer (Z) formation process in which a copper oxide layer (Z) is formed by oxidation treatment on electronic components that have copper pillars (X). A silicon compound layer (Y) formation process for forming a silicon compound layer (Y) on an electronic component having a copper pillar (X) by water glass treatment and / or silane coupling treatment.

[0103] Pre-treatment process The pretreatment step is a step of performing a pretreatment on an electronic component having a copper pillar (X). Here, the pretreatment is a treatment for removing dirt on the surface of the copper pillar (X) and an oxide film due to natural oxidation, and examples of the pretreatment include (1) a treatment of immersing the electronic component in a strong base aqueous solution such as a sodium hydroxide aqueous solution, (2) a treatment of immersing the electronic component in a strong acid aqueous solution such as a sulfuric acid aqueous solution, and (3) a treatment of washing (rinsing) the electronic component with water. The pretreatment step may be performed by at least one treatment selected from the group consisting of the above (1) to (3). Moreover, when the pretreatment step is performed by two or more treatments, the order of the treatments is not particularly limited and can be selected appropriately.

[0104] The copper oxide layer (Z) forming step is a step of forming a copper oxide layer (Z) on an electronic component having a copper pillar (X) by oxidation treatment. The oxidizing agent used in the oxidation treatment is not particularly limited, but for example, an aqueous solution containing sodium chlorite, potassium chlorite, sodium hypochlorite, potassium hypochlorite, sodium chlorate, potassium chlorate, sodium perchlorate, potassium perchlorate, or the like is preferable, and an aqueous solution containing sodium chlorite is more preferable. The oxidizing agent may be used together with an alkaline compound such as sodium hydroxide, potassium hydroxide, sodium carbonate, or potassium carbonate. The amount of the alkaline compound added to the oxidizing agent is not particularly limited, but is preferably 1 to 60 parts by mass, more preferably 5 to 40 parts by mass, relative to 100 parts by mass of the oxidizing agent.

[0105] The oxidizing agent may be used with the addition of a surface active molecule or an additive (e.g., a phosphate such as trisodium phosphate dodecahydrate). The surface active molecule is not particularly limited, but may be, for example, a porphyrin-based surface active molecule such as porphyrin, porphyrin macrocycle, expanded porphyrin, ring-contracted porphyrin, linear porphyrin polymer, porphyrin sandwich coordination complex, or porphyrin array; silane, tetraorgano-silane, aminoethyl-aminopropyltrimethoxysilane, (3-aminopropyl)trimethoxysilane, 1-[3-(trimethoxysilyl)propyl]urea), (3-aminopropyl)triethoxysilane, (3-glycidyloxypropyl)trimethoxysilane (3-glycidoxypropyltrimethoxysilane); Examples of the surface active molecules include silane-based surface active molecules such as (silane), (3-chloropropyl)trimethoxysilane, (3-glycidyloxypropyl)trimethoxysilane, dimethyldichlorosilane, 3-(trimethoxysilyl)propyl methacrylate, ethyltriacetoxysilane, triethoxy(isobutyl)silane, triethoxy(octyl)silane, tris(2-methoxyethoxy)(vinyl)silane, chlorotrimethylsilane, methyltrichlorosilane, silicon tetrachloride, tetraethoxysilane, phenyltrimethoxysilane, chlorotriethoxysilane, and ethylene-trimethoxysilane; amines; and sugars. By adding the surface active molecules or the additives to the oxidizing agent, etching of the copper pillar is suppressed, and the oxide layer tends to have a protrusion of an appropriate length. The amount of the surface active molecules to be added to the oxidizing agent is not particularly limited, but is preferably 0.1 to 20 parts by mass, and more preferably 1 to 10 parts by mass, relative to 100 parts by mass of the oxidizing agent. The amount of the additive added to the oxidizing agent is not particularly limited, but is preferably 0.1 to 20 parts by mass, and more preferably 1 to 10 parts by mass, relative to 100 parts by mass of the oxidizing agent.

[0106] When silane-based surface-active molecules are used as the surface-active molecules added to the oxidizing agent, the silane-based surface-active molecules can be chemically bonded to the copper pillar (X). However, the amount of the bond is small, and it is present in a trace amount inside the copper oxide layer (Z), and is not enough to form a silicon compound layer (Y). That is, in the embodiment in which the oxidizing agent to which the silane-based surface-active molecules are added is used in the oxidation treatment, the silicon compound layer (Y) cannot be formed. In the above embodiment, in elemental analysis by XPS, the content of Si2p measured from the copper oxide layer (Z) is, for example, 0.1 at% or less with respect to the total of the detected components.

[0107] The liquid temperature in the oxidation treatment is not particularly limited, but is preferably, for example, 40 to 95° C., and more preferably, 45 to 80° C. The treatment (reaction) time in the oxidation treatment is not particularly limited, but is preferably, for example, 0.5 to 30 minutes, and more preferably, 1 to 10 minutes. The concentration of the oxidizing agent used in the oxidation treatment is not particularly limited, but is preferably, for example, 1 g / L or more, more preferably 5 g / L or more, and even more preferably 10 g / L or more.

[0108] In the copper oxide layer (Z) forming step, an electronic component having a copper pillar (X) is subjected to an oxidation treatment, whereby fine irregularities can be formed on the surface of the copper oxide layer (Z). The copper oxide layer (Z) has fine irregularities on its surface, which improves the wettability of the copper oxide layer (Z) and facilitates the formation of the silicon compound layer (Y). In addition, the wettability of the formed silicon compound layer (Y) is also improved, and the epoxy resin composition adheres closely without gaps, so that high adhesion and bonding tend to occur between the silicon compound layer (Y) and the sealing body (cured product) even after the epoxy resin composition is cured.

[0109] Furthermore, since the copper oxide layer (Z) has fine irregularities on its surface, the silicon compound layer (Y) also has fine irregularities on its surface, and the sealing body enters the fine irregularities to exert an anchor effect, which tends to result in high adhesion and adhesion between the silicon compound layer (Y) and the sealing body. Furthermore, since the silicon compound layer (Y) has fine irregularities on its surface, the area of ​​the silicon compound layer (Y) in contact with the epoxy resin composition increases, and the chemical bond between the epoxy resin composition and the silicon compound layer (Y) increases, which tends to result in high adhesion and adhesion between the silicon compound layer (Y) and the sealing body. As a result of the above, it is believed that delamination is suppressed.

[0110] As an example of the "electronic component connection process" described later, a process of soldering the copper pillar (X) of the electronic component of the present invention to the substrate by reflow processing is described, but in this process, the solder may creep up to the fine irregularities present on the surface of the copper oxide layer (Z), which may result in delamination. However, even in such a case, by adjusting the solder components to suppress the solder creep up, it is possible to enjoy only the effect of suppressing delamination by improving the wettability of the copper oxide layer (Z).

[0111] In the copper oxide layer (Z) forming step, the copper oxide layer (Z) may be formed by oxidation treatment, and then the formed copper oxide may be subjected to reduction treatment. For example, copper oxide (CuO) may be formed by oxidation treatment, and then cuprous oxide (CuO) may be formed by reduction treatment. In the reduction treatment, a solution containing a reducing agent is used, and examples of the reducing agent that can be used include DMAB (dimethylamine borane), diborane, sodium borohydride, and hydrazine. In addition, examples of the solution containing a reducing agent include a liquid containing a reducing agent, an alkaline compound (sodium hydroxide, potassium hydroxide, etc.), and a solvent (pure water, etc.). By performing the reduction treatment, the number and length of irregularities on the surface of the oxide layer (Z) can be adjusted.

[0112] In the copper oxide layer (Z) forming step, after the copper oxide layer (Z) is formed by oxidation treatment, the formed copper oxide may be subjected to dissolution treatment. For example, a method of treating the surface of the copper oxide layer (Z) with a dissolving agent capable of dissolving copper oxide may be mentioned.

[0113] In the electronic component of the present invention, the copper oxide layer (Z) is provided on a part or the whole of the surface of the copper pillar (X) through the copper oxide layer (Z) forming step.

[0114] The silicon compound layer (Y) forming step is a step of forming a silicon compound layer (Y) on an electronic component having a copper pillar (X) by a water glass treatment and / or a silane coupling treatment. In the electronic component of the present invention, the silicon compound layer (Y) covering at least a part of the copper pillar (X) is formed through the silicon compound layer (Y) forming step.

[0115] The water glass treatment is carried out, for example, by immersing an electronic component having copper pillars (X) in a water glass solution at 50 to 100° C. (preferably 60 to 90° C.) for 0.3 to 10 minutes (preferably 0.5 to 6 minutes). The water glass solution may be a 0.1 to 15 mass % (preferably 1 to 10 mass %) aqueous solution of sodium silicate, and the SiO2 / Na2O (molar ratio) is not particularly limited, but is, for example, 2 to 2.5.

[0116] The silane coupling treatment is carried out, for example, by immersing an electronic component having a copper pillar (X) in a silane coupling agent at 10 to 40° C. (preferably 20 to 30° C.) for 0.1 to 10 minutes (preferably 0.3 to 5 minutes). Examples of the silane coupling agent include 3-aminopropyltriethoxysilane, 3-glycidoxypropyltrimethoxysilane, 3-aminopropyltrimethoxysilane, and 3-mercaptopropylmethyldimethoxysilane.

[0117] In the silicon compound layer (Y) forming step, after forming the silicon compound layer (Y) by water glass treatment and / or silane coupling treatment, the silicon compound layer (Y) may be washed with water and / or dried. When both water glass treatment and silane coupling treatment are performed in the formation of the silicon compound layer (Y), the order is not particularly limited. When both water washing and drying treatments of the silicon compound layer (Y) are performed after the formation of the silicon compound layer (Y), the order is not particularly limited. The purpose of the drying treatment is to dry the electronic component and to promote the coupling reaction when the silane coupling treatment is performed. The drying treatment is performed, for example, by drying the electronic component at 100 to 200°C for 0.1 to 10 minutes.

[0118] 1(a) to 1(c) are cross-sectional views showing an embodiment of the manufacturing method of an electronic component of the present invention. First, an electronic component 1 having a copper pillar 2 is prepared. The copper pillar 2 is provided on the surface of the electronic component 1 and is connected to an electrode portion 3 (FIG. 1(a)). An example of the electronic component 1 is one having a copper pillar on a semiconductor chip. A copper oxide layer 4 is formed on the electronic component 1 by oxidation treatment (FIG. 1(b)). Thereafter, a silicon compound layer 5 is formed by water glass treatment and / or silane coupling treatment (FIG. 1(c)). In this embodiment, a mode in which a water glass treatment and / or a silane coupling treatment is performed after the oxidation treatment is shown, but the water glass treatment and / or the silane coupling treatment may be performed on the electronic component 1 without performing the oxidation treatment. That is, the electronic component of the present invention may be a mode in which a silicon compound layer 5 is formed on the copper pillar 2 without forming a copper oxide layer 4.

[0119] 2(a) and (b) are cross-sectional views showing another embodiment of the method for manufacturing an electronic component of the present invention. First, an electronic component 11 is prepared, which includes a copper pillar 12 having a solder bump 13 at its tip. The copper pillar 12 is provided on the surface of the electronic component 11, and is connected to an electrode portion 14 (FIG. 2(a)). An example of the electronic component 11 is a semiconductor chip having a copper pillar having a solder bump at its tip. The electronic component 11 is subjected to a water glass treatment and / or a silane coupling treatment to form a silicon compound layer 15 (FIG. 2(b)). Although the oxidation treatment is not described in this embodiment, the method may include a step of forming a copper oxide layer by performing an oxidation treatment on the copper pillar 12.

[0120] [Mounting board and its manufacturing method] The mounting board of the present invention includes the electronic component of the present invention, a substrate having an electrode portion and connected to the electronic component via a copper pillar (X), and a sealing body located between the electronic component and the substrate. As described above, the sealing body is made of a liquid sealant (liquid sealing material) such as an underfill, a film-like sealing material, or a granular sealing material. Here, an embodiment in which the sealing body is a cured product of the underfill will be described in detail, but the present invention is not limited to the above embodiment.

[0121] The underfill is not particularly limited as long as it is used as a semiconductor encapsulant, and may be, for example, an epoxy resin composition. The epoxy resin composition is characterized by containing an epoxy resin, and may further contain a curing agent, an inorganic filler, etc. When the underfill is an epoxy resin composition, the effect of suppressing delamination between the encapsulant and the copper pillar after reflow is particularly improved.

[0122] Although the reason is not clear, it is considered to be due to the high adhesion and bonding between the silicon compound layer (Y) in the electronic component of the present invention and the cured product of the epoxy resin composition. The reason for the high adhesion and bonding between the silicon compound layer (Y) and the cured product is, for example, the presence of a chemical bond between the silicon compound contained in the silicon compound layer (Y) and the epoxy resin contained in the epoxy resin composition. That is, when the epoxy resin composition is injected as an underfill between the electronic component of the present invention and the substrate and heated to form a sealing body (cured product), the silicon compound reacts with the epoxy group of the epoxy resin to form a chemical bond, and it is considered that high adhesion and bonding are exhibited between the silicon compound layer (Y) and the cured product. In addition, when the silicon compound layer (Y) is formed by silane coupling treatment, it is considered that the reactive functional group (e.g., amino group, epoxy group, thiol group, (meth)acryloyl group, etc.) of the silane coupling agent used reacts with the epoxy group of the epoxy resin to form a chemical bond.

[0123] Another reason is that the formation of the silicon compound layer (Y) improves wettability, and the surface of the silicon compound layer (Y) and the epoxy resin composition are tightly adhered to each other without any gaps, so that high adhesion and bonding properties are exhibited between the silicon compound layer (Y) and the cured product even after the epoxy resin composition is cured.

[0124] Examples of epoxy resins include aromatic epoxy resins and aliphatic epoxy resins. The number of epoxy groups in the epoxy resin is not particularly limited as long as it is 1 or more, but is preferably 2 or more (i.e., a polyfunctional epoxy resin). The epoxy resins can be used alone or in combination of two or more.

[0125] The aromatic epoxy resin is not particularly limited as long as it is an epoxy resin having a structure containing an aromatic ring such as a benzene ring, but examples thereof include bisphenol A type epoxy resin, bisphenol F type epoxy resin, novolac type epoxy resin, fluorene type epoxy resin, biphenyl aralkyl epoxy resin, diepoxy resin such as 1,4-phenyldimethanol diglycidyl ether, biphenyl type epoxy resin such as 3,3',5,5'-tetramethyl-4,4'-diglycidyloxybiphenyl, glycidylamine type epoxy resin such as diglycidylaniline, diglycidyl toluidine, tetraglycidyl-m-xylylenediamine, aminophenol type epoxy resin such as triglycidyl-p-aminophenol, and naphthalene ring-containing epoxy resin. Among them, bisphenol A type epoxy resin, bisphenol F type epoxy resin, biphenyl type epoxy resin, aminophenol type epoxy resin, and naphthalene ring-containing epoxy resin are preferred.

[0126] The aliphatic epoxy resin is not particularly limited, and examples thereof include diepoxy resins such as polytetramethylene glycol diglycidyl ether, butanediol diglycidyl ether, neopentyl glycol diglycidyl ether, trimethylolpropane diglycidyl ether, glycerin diglycidyl ether, and neopentyl glycol diglycidyl ether; triepoxy resins such as trimethylolpropane triglycidyl ether and glycerin triglycidyl ether; vinyl(3,4-cyclohexyl)ether; alicyclic epoxy resins such as 2-(3,4-epoxycyclohexyl)-5,1-spiro-(3,4-epoxycyclohexyl)-m-dioxane; glycidylamine-type epoxy resins such as tetraglycidylbis(aminomethyl)cyclohexane; hydantoin-type epoxy resins such as 3-diglycidyl-5-methyl-5-ethylhydantoin; and epoxy resins having a silicone skeleton such as 1,3-bis(3-glycidoxypropyl)-1,1,3,3-tetramethyldisiloxane.

[0127] The curing agent is not particularly limited as long as it initiates or advances the polymerization of the epoxy resin, and examples thereof include amine-based curing agents, acid anhydride-based curing agents, phenol-based curing agents, and imidazole-based curing agents. The curing agents may be used alone or in combination of two or more.

[0128] Examples of the amine-based curing agent include aromatic amines such as methylenedianiline, m-phenylenediamine, 4,4'-diaminodiphenylsulfone, 4,4'-diamino-3,3'-diethyldiphenylmethane, diethyltoluenediamine, dimethylthiotoluenediamine, and 3,3'-diaminodiphenylsulfone. Examples of the acid anhydride-based curing agent include alkylated tetrahydrophthalic anhydrides such as methyltetrahydrophthalic anhydride and methylhexahydrophthalic anhydride, hexahydrophthalic anhydride, methylhymic anhydride, dodecenyl succinic anhydride, and methylnadic anhydride. Examples of the phenol-based curing agent include phenol novolac resin, cresol novolac resin, naphthol-modified phenolic resin, dicyclopentadiene-modified phenolic resin, and p-xylene-modified phenolic resin. Examples of the imidazole-based hardener include 2-methylimidazole, 2-undecylimidazole, 1-cyanoethyl-2-undecylimidazole, 2-heptadecylimidazole, 2-ethyl-4-methylimidazole, 1-cyanoethyl-2-ethyl-4-imidazole, 2-phenylimidazole, and 2-phenyl-4-methylimidazole. Examples of the imidazole-based hardener include microcapsule-type imidazole-based hardener.

[0129] The epoxy resin composition as the underfill can be prepared by a known and commonly used method, for example, by introducing the epoxy resin, the curing agent, and other components such as inorganic fillers, if necessary, into an appropriate mixer simultaneously or separately, and stirring and mixing while melting by heating if necessary.

[0130] The method for manufacturing the mounting substrate is not particularly limited, but may include, for example, the following steps. An electronic component connecting step for connecting the copper pillar (X) of the electronic component of the present invention to the electrode portion of a substrate having the electrode portion. An encapsulation forming process in which an underfill is injected between the electronic component and the substrate, and the underfill is heated and cured to form an encapsulation.

[0131] The electronic component connection step may be a step of solder-joining the copper pillar (X) of the electronic component of the present invention to the substrate by reflow processing. In this case, the copper pillar (X) of the electronic component of the present invention is provided with a solder bump at its tip, or a solder bump is provided on the surface of the electrode part of the substrate, so that the copper pillar (X) and the substrate are solder-joined by reflow processing. The reflow processing is not particularly limited, but a reflow furnace is usually used. The temperature of the reflow processing (solder bonding temperature) is, for example, 180 to 290°C.

[0132] In the sealing body forming step, the heating temperature of the underfill is not particularly limited, but is preferably, for example, 60 to 200° C., and more preferably 80 to 160° C. The heating time is not particularly limited, but is preferably, for example, 0.1 to 5 hours, and more preferably 0.5 to 3 hours.

[0133] 3(a) to (c) are cross-sectional views showing an embodiment of the method for manufacturing a mounting board of the present invention. First, an electronic component 21 is prepared, which includes a copper pillar 23 having a silicon compound layer 24 formed on the surface. The copper pillar 23 is provided on the surface of the electronic component 21, and is connected to an electrode portion 22. A wiring board 27 having an electrode portion 26 is also prepared, and a solder bump 25 is formed on the electrode portion 26. The surface of the electronic component 21 on which the copper pillar 23 is formed is positioned so as to face the solder bump 25 on the wiring board 27, and alignment is performed (FIG. 3(a)). Next, the copper pillar 23 (the silicon compound layer 24) and the solder bump 25 are joined and heated to connect (reflow process) (FIG. 3(b)). An underfill 28 is injected into the space formed between the electronic component 21 and the wiring board 27, and is heated and cured to form a sealing body (cured product), thereby obtaining a mounting board (FIG. 3(c)). In FIG. 3, the method for manufacturing a mounting board of the present invention is described using an electronic component having a copper pillar with a silicon compound layer formed on the surface thereof. However, the electronic component may have a copper oxide layer between the copper pillar and the silicon compound layer.

[0134] 4(a) to (c) are cross-sectional views showing another embodiment of the method for manufacturing a mounting board of the present invention. First, an electronic component 31 is prepared, which includes a copper pillar 33 having a solder bump 35 at its tip and a silicon compound layer 34 formed on the surface. The copper pillar 33 is provided on the surface of the electronic component 31 and is connected to an electrode portion 32. A wiring board 37 having an electrode portion 36 is also prepared. The surface of the electronic component 31 on which the copper pillar 33 is formed is positioned so as to face the electrode portion 36 of the wiring board 37, and alignment is performed (FIG. 4(a)). Next, the solder bump 35 (the silicon compound layer 34 on the surface) and the electrode portion 36 are joined and heated to connect (reflow process) (FIG. 4(b)). An underfill 38 is injected into the space formed between the electronic component 31 and the wiring board 37, and the underfill 38 is heated and cured to form a sealing body (cured product), thereby obtaining a mounting board (FIG. 4(c)). In FIG. 4, the method for manufacturing a mounting board of the present invention is described using an electronic component having a copper pillar with a solder bump at its tip and a silicon compound layer formed on its surface. However, the electronic component may have a copper oxide layer between the copper pillar and the silicon compound layer. EXAMPLES

[0135] The present invention will be described in more detail below based on examples, but the present invention is not limited to these examples.

[0136] Examples of the epoxy resin composition of the present invention will now be described.

[0137] (Preparation of Epoxy Resin Composition) The epoxy resin compositions of Examples A1 to A12 and Comparative Examples A1 and A2 were prepared by mixing the epoxy resin (A), epoxy resin (B), curing agent (C), and inorganic filler (D) using a roll mill so as to obtain the blending ratios shown in Table 1 below. The numerical values ​​for each component in Table 1 represent parts by mass. For YA010AJGP, the mass of nanosilica alone is listed, and the bisphenol F epoxy resin contained in this product is the same as "YDF8170," and its mass is listed. Epoxy resin (A) LITE514SE (product name): A bifunctional cardanol-based epoxy resin, which is a compound represented by the above formula (CAC1), with an epoxy equivalent of 440 g / eq, manufactured by Cardlite Co., Ltd. NC-547 (product name): A trifunctional cardanol-based epoxy resin, which is a compound represented by the above formula (CAC2), with an epoxy equivalent of 800 g / eq, manufactured by Cardlight Co., Ltd. EPOGOSE HD (product name): 1,6-Hexanediol diglycidyl ether, epoxy equivalent 155g / eq, manufactured by Yokkaichi Chemical Co., Ltd. Epoxy resin (B) YDF8170 (product name): Bisphenol F type epoxy resin, epoxy equivalent 160g / eq, manufactured by Nippon Steel Chemical & Material Co., Ltd. jER630 (product name): Aminophenol type epoxy resin, epoxy equivalent 98g / eq, manufactured by Mitsubishi Chemical Corporation EP 3980S (product name): Glycidylamine type epoxy resin, epoxy equivalent 115g / eq, manufactured by ADEKA Corporation Hardener (C) 2P4MZ (product name): 2-phenyl-4-methylimidazole, manufactured by Shikoku Kasei Co., Ltd. KAYAHARD AA (product name): Amine-based hardener, equivalent weight 64g / eq, manufactured by Nippon Kayaku Co., Ltd. YH307 (product name): Acid anhydride curing agent, equivalent weight 234g / eq, manufactured by Mitsubishi Chemical Corporation MEH-8005 (product name): Phenol-based hardener, equivalent weight 133-138g / eq, manufactured by Meiwa Chemical Industry Co., Ltd. ·Inorganic filler (D) SE605H-SMG: Average particle size 2μm, silica, 3-methacryloxypropyltrimethoxysilane treatment, manufactured by Admatechs Co., Ltd. SE1050SEO: Average particle size 0.3 μm, silica, 3-glycidoxypropyltrimethoxysilane treatment, manufactured by Admatechs Co., Ltd. YA010AJGP: Masterbatch of nano-silica with an average particle size of 10 nm and bisphenol F type epoxy resin (weight ratio of the former to the latter = 3:7), surface treated with 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, manufactured by Admatechs Co., Ltd.

[0138] (Evaluation A1: Measurement of water absorption rate) The epoxy resin composition was cured at 150°C for 120 minutes to obtain test piece 1. Test piece 1 was then placed in a PCT test tank (121°C±2°C / humidity 100% / 2atm) for 20 hours, and then cooled to room temperature (25°C) to obtain test piece 2. The mass of test piece 1 was W0 (g) and the mass of test piece 2 was W1 (g), and the water absorption of the cured product was calculated using the following formula. The results are shown in the "Water absorption (%)" column of the evaluation results in Table 1. Water absorption rate (%)=(W1-W0) / W0×100(%)

[0139] (Evaluation A2: Elastic modulus at 25°C) The epoxy resin composition was cured at 150°C for 120 minutes to obtain a test piece 3, and the elastic modulus (GPa, 25°C) of this test piece 3 was measured by DMA (Dynamic Mechanical Analysis) using a DMS6100 from SII Corporation. The results are shown in the "Elastic modulus at 25°C (GPa)" section of the evaluation results in Table 1.

[0140] [Table 1]

[0141] Hereinafter, an embodiment of the electronic component of the present invention will be described. The following processes were performed on a Si chip equipped with copper pillars, with each process being described in order.

[0142] (1) Preparation of Si chip with copper pillars In Examples B1 to B11 and Comparative Examples B2 and B3, a TEG for evaluation (ALTS-TEGFC150JY(PI), Cu 30 μm+SnAg 15 μm, manufactured by Waltz Corporation) was used as a Si chip having a copper pillar. Note: No surface treatment was performed on Comparative Example B1.

[0143] (2) Pretreatment In Examples B7 to B11 and Comparative Examples B2 and B3, the Si chip was degreased by immersing it in a 40 g / L aqueous sodium hydroxide solution at a liquid temperature of 50° C. for 1 minute to remove dirt on the copper pillar surface. Thereafter, the surface of the Si chip (copper pillar surface) was washed with water. Next, the Si chip that had been degreased was immersed in a 10 mass % aqueous sulfuric acid solution at a liquid temperature of 25° C. for 2 minutes to remove the oxide film on the copper pillar surface of the Si chip. Thereafter, the surface of the Si chip (copper pillar surface) was washed with water. Furthermore, the Si chip was immersed in a 1.2 g / L aqueous sodium hydroxide solution (pH 10.5) at 40° C. for 1 minute to be washed.

[0144] (3) Oxidation treatment In Examples B7 to B11 and Comparative Examples B2 and B3, the pretreated Si chips were subjected to oxidation treatment under the oxidation conditions shown in Table 2, thereby forming fine convex portions on the surfaces (copper pillar surfaces) of the Si chips. After that, the chips were washed with water at room temperature for 1 minute. Note: In Examples B1 to B6, (2) pretreatment and (3) oxidation treatment were not carried out.

[0145] (4) Water glass treatment In Examples B1, B6, B7, and B9 to B11, the Si chips were immersed in a water glass solution and subjected to water glass treatment under the reaction conditions shown in Table 2. The water glass used was a 3 mass% aqueous solution of sodium silicate (SiO2 / Na2O (molar ratio) = 2.06 to 2.31). The chips were then washed with water and dried in a dryer at 100°C for 1 minute.

[0146] (5) Silane coupling treatment In Examples B2 to B11, the Si chip was immersed in a silane coupling solution and subjected to a silane coupling treatment under the reaction conditions described in Table 2. The silane coupling agents used were KBE-903 (3-aminopropyltriethoxysilane, manufactured by Shin-Etsu Chemical Co., Ltd.), KBM-403 (3-glycidoxypropyltrimethoxysilane, manufactured by Shin-Etsu Chemical Co., Ltd.), KBM-903 (3-aminopropyltrimethoxysilane, manufactured by Shin-Etsu Chemical Co., Ltd.), and KBM-802 (3-mercaptopropylmethyldimethoxysilane, manufactured by Shin-Etsu Chemical Co., Ltd.). After the silane coupling treatment, the chip was washed with water and dried in a dryer at 110°C for 1 minute.

[0147] (Rating B1: Average surface elevation difference) The average height difference of the copper pillar surface was calculated for the Si chips of Examples B1 to B11 and Comparative Examples B1 to B3. A specific description will be given below with reference to Figs. 5 and 6. Fig. 5 is a "cross-sectional image of the copper pillar in the perpendicular direction to the silicon compound layer (treated surface)" in Example B10, taken with a scanning electron microscope (SEM), with a magnification of 30,000 times. Fig. 6 is a schematic diagram of Fig. 5, in which 42 is the surface of the silicon compound layer (treated surface), 43 and 44 are the two lowest recesses in the image, L1 is a straight line tangent to the two lowest recesses in the image, 45 is the highest protrusion in the image, L2 is a straight line tangent to the highest protrusion 45 in the image and parallel to the straight line L1, and D is the perpendicular distance (height difference) between the straight lines L1 and L2. In addition, the perpendicular distance (height difference) was measured for five different locations of the copper pillar in the same manner. The average value of these was calculated to calculate the average height difference of the copper pillar surface. The results are shown in the evaluation results in Table 2 under "Surface height difference (nm)".

[0148] (Evaluation B2: Analysis by XPS) The Si chips of Examples B1 to B11 and Comparative Examples B1 to B3 were analyzed for the constituent elements of the copper pillar surface under the conditions described in Table 3 using Quantera SXM (manufactured by ULVAC-PHI). Of the detected components, N1s (x20), Na1s (x20), Si2p (x15), and Cu2p3 (x7) (number of sweeps is in parentheses) were analyzed. The results are shown in the "XPS Narrow spectrum" of the evaluation results in Table 2. Note that other detected components are indicated as "Other" in the table. The atomic percentage of each component was calculated with the total atomic percentage of all detected components being 100%.

[0149] XPS measurement conditions Equipment: QuanteraSXM (made by ULVAC-PHI) Ultimate vacuum: 6.7×10 -8 Pa or less Excitation source: Monochromated AlKα Excitation source energy: 1486.6 eV Output: 25W (X-ray scanning method) Detection area: 800 x 400um Incident angle: 90° Take-off angle: 45° Neutralization gun: Yes Sputtering conditions: Ion species: Ar+ Acceleration voltage: 1 kV

[0150] (Rating B3:TOF-SIMS) For the Si chips of Examples B1 to B11 and Comparative Examples B1 to B3, mass analysis of the components on the copper pillar surface was performed using a TRIFT V nano-TOF (manufactured by ULVAC-PHI, Inc.) under the following conditions. The presence or absence of peaks corresponding to the molecular weight of silicon compounds (SiOx, HSiOx, etc.) in the obtained fragment ions is recorded in "TOF-SIMS" in Table 2. If a peak corresponding to the molecular weight of a silicon compound is present, it is marked with "◯", and if not, it is marked with "×".

[0151] TOF-SIMS measurement conditions Mode: Negative Primary ion: 30kV, Bi3++ Measurement mode: Bunching Mass range: 0-1850u Raster size: 100μm×100μm Measurement time: 30 frames / 1 field of view Charge neutralization: None Number of pixels: 512 x 512 pixels GCIB:-

[0152] (Evaluation B4: Probability of delamination after reflow) The Si chips of Examples B1 to B11 and Comparative Examples B1 to B3 were mounted on a substrate (WALTS KIT 01A150P-10 SAC specification, manufactured by Waltz Corporation), and underfill (an epoxy resin composition containing bisphenol F type epoxy resin, product name: U8410-207R6, manufactured by Namics Corporation) was injected at 110°C and cured at 150°C for 2 hours. The mounted Si chip was then dried at 150°C for 30 minutes and passed through a reflow furnace with a maximum temperature of 260°C five times. The cross section of the mounted Si chip after reflow was observed at 1000 times using a scanning electron microscope (SEM), and the number of delaminations between the copper pillars and the sealing body (cured underfill) was counted. The copper pillars observed were located at the outermost position of the Si chip. That is, the number of delaminations was observed for the copper pillars located at the outermost position of the Si chip and aligned in a row. The reason for observing the copper pillars above is that in the mounted Si chip, the copper pillars at the above positions are most susceptible to stress and are most likely to cause delamination. 61 pieces were observed. The "delamination occurrence probability (%)" was calculated using the following formula and is listed in Table 2. Probability of delamination (%) = Number of delaminations (pieces) / Number of observations (61 pieces)

[0153] [Table 2] [Explanation of symbols]

[0154] 1. Electronic Components 2 Copper pillar 3 Electrode part 4 Copper oxide layer 5 Silicon Compound Layer 11 Electronic Components 12 Copper pillar 13 Solder Bumps 14 Electrode section 15 Silicon Compound Layer 21 Electronic Components 22 Electrode section 23 Copper Pillar 24 Silicon Compound Layer 25 Solder Bumps 26 Electrode section 27 Wiring board 28 Underfill 31 Electronic Components 32 Electrode section 33 Copper Pillar 34 Silicon Compound Layer 35 Solder Bumps 36 Electrode section 37 Wiring board 38 Underfill 41 Cross-sectional image perpendicular to the silicon compound layer (treated surface) 42 Surface of silicon compound layer (treated surface) 43 The lowest recess in the image 44 Lowest recess in the image 45 Highest protrusion in the image D The vertical distance between lines L1 and L2 (height difference) L1 Straight line tangent to the two lowest concave points in the image L2 A straight line parallel to the straight line L1 passing through the highest convexity 45 in the image

Claims

1. (A) an epoxy resin having an aliphatic hydrocarbon group having 5 or more carbon atoms; an epoxy resin (B) other than the epoxy resin (A); A curing agent (C), and Inorganic filler (D), 1. An epoxy resin composition comprising:

2. 2. The epoxy resin composition according to claim 1, wherein the epoxy resin (A) has an aliphatic hydrocarbon group having 5 to 20 carbon atoms.

3. The epoxy resin composition according to claim 1 or 2, wherein the epoxy resin (A) has two or more epoxy groups.

4. 3. The epoxy resin composition according to claim 1, wherein the epoxy resin (A) is a cardanol-based epoxy resin.

5. 3. The epoxy resin composition according to claim 1, wherein the content of the epoxy resin (A) is 5 to 80 mass% based on the total epoxy resins (100 mass%) contained in the epoxy resin composition.

6. 3. The epoxy resin composition according to claim 1, wherein the curing agent (C) is at least one selected from the group consisting of an amine-based curing agent, an acid anhydride-based curing agent, a phenol-based curing agent, and an imidazole-based curing agent.

7. The epoxy resin composition according to claim 1 or 2, wherein the content of the inorganic filler (D) is 40 to 70 mass% relative to the epoxy resin composition (100 mass%).

8. 3. The epoxy resin composition according to claim 1, which is used for encapsulating a semiconductor.

9. A cured product of the epoxy resin composition according to claim 1 or 2.

10. A semiconductor device comprising: a substrate; a semiconductor element disposed on the substrate; and the cured product according to claim 9 that encapsulates the semiconductor element.

Citation Information

Patent Citations

  • Epoxy resin composition and cured product of the same

    JP2014201639A

  • Epoxy resin composition

    JP2021036019A

  • Resin sheet for semiconductor chip adhesion

    JP2023002324A

  • Resin composition

    JP2024075484A

  • Epoxy resin composition

    WO2022270536A1